Microbiota of the Esophagus and Stomach in Patients with Gastroesophageal Reflux Disease and Healthy Volunteers - D. E. Rumyantseva; A. S. Trukhmanov; A. V. Kudryavtseva; G. S. Krasnov; A. V. Paraskevova; O. A. Storonova; A. B. Ponomarev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
This paper is aimed at investigating the microbiota of the esophagus and stomach in patients with gastroesophageal reflux disease (GERD) and healthy volunteers.Materials and methods.  The study included 15 patients suffering from GERD and 6 healthy volunteers. All subjects underwent sampling of esophageal and gastric contents. The study of the microbiota in the obtained samples was performed by sequencing the 16S gene of ribosomal RNA (rRNA).Results.  The most common types of bacteria in the esophagus and stomach in patients with GERD and healthy volunteers are found to be Bacteroidetes, Firmicutes, Actinobacteria, Proteobacteria, Fusobacterium. By comparing the relative contents of the main types of bacteria in the esophageal mucus and gastric contents, a significant decrease in the proportion of Proteobacteria was observed in patients with GERD as compared to healthy volunteers. The decrease in the relative number of bacteria belonging to the Acetobacteraceae, Bacillaceae, Bdellovibrionaceae, Clostridiales Insertae Sedis XI, Fusobacteriaceae, Moraxellaceae, Pasteurellaceae and Rhodocyclaceae families was observed in the esophagus in patients with GERD as compared to healthy volunteers. A higher bacterial content of the Leptotrichiaceae and Veillonellaceae families was detected in the stomach of patients with GERD.Conclusions.  The obtained results indicate differences in the intraluminal microbiota of the esophagus and stomach in patients with GERD and healthy volunteers. Further study should be carried out to study the effect of changes in bacterial composition on those in the esophagus and stomach.